Ice Nucleating Particles Carried From Below a Phytoplankton Bloom to the Arctic Atmosphere. Issue 14 (31st July 2019) - Creamean, J. M.; Cross, J. N.; Pickart, R.; McRaven, L.; Lin, P.; Pacini, A.; Hanlon, R.; Schmale, D. G.; Ceniceros, J.; Aydell, T.; Colombi, N.; Bolger, E.; et al.
Abstract: As Arctic temperatures rise at twice the global rate, sea ice is diminishing more quickly than models can predict. Processes that dictate Arctic cloud formation and impacts on the atmospheric energy budget are poorly understood, yet crucial for evaluating the rapidly changing Arctic. In parallel, warmer temperatures afford conditions favorable for productivity of microorganisms that can effectively serve as ice nucleating particles (INPs). Yet the sources of marine biologically derived INPs remain largely unknown due to limited observations. Here we show, for the first time, how biologically derived INPs were likely transported hundreds of kilometers from deep Bering Strait waters and upwelled to the Arctic Ocean surface to become airborne, a process dependent upon a summertime phytoplankton bloom, bacterial respiration, ocean dynamics, and wind‐driven mixing. Given projected enhancement in marine productivity, combined oceanic and atmospheric transport mechanisms may play a crucial role in provision of INPs from blooms to the Arctic atmosphere. Key Points: A persistent phytoplankton bloom in Bering Strait spurred production of microorganisms that produced ice nucleating particles Biologically derived ice nucleating particles were vertically transported from the floor to the surface waters of the Arctic Ocean Ocean and lower atmosphere dynamics played a key role in transporting and aerosolizing the biologically derived ice nucleating particles